Town and Monastery in the Carolingian Period - McKitterick, Rosamond (Studies in church history, 1979)
Although there were both urban and rural monastic communities in the Frankish kingdoms in the Carolingian period, far more is known about the landed monasteries in the countryside regarding both their internal organisation and the relationship between them and the rural community in which they lived and over which they were the lords. The statutes of Adalhard of Corbie for example provide information concerning the monastery both within the monastic community and on its estates, and show us the abbey as the centre of an agricultural region. The monasteries in the towns on the other hand are much less well-documented and the evidence for Carolingian towns themselves is both sparse and difficult to interpret. If a town is understood to be ‘a concentration of population larger than the neighbouring agricultural settlements in which there is a substantial non-agricultural population which may be concerned with defence, administration, religion, commerce or industry’, there are not very many Carolingian centres for which enough evidence survives to justify their being called towns. Valenciennes for example, described recently as une ville carolingienne, is mentioned in the sources occasionally as a portus and seems to have succeeded Farrars in importance in the region sometime in the eighth century. In the time of Charles the Bald it had a mint, and Charlemagne, Charles the Bald, Lothar I and Lothar II are all known to have issued charters from a royal palatium at Valenciennes. There were several churches and the abbey of St Salvius in the settlement, and it is likely that some trading activity went on. But other than that Valenciennes was a settlement which carried on some sort of economic activity, very little is known. The abbey of St Amand, a rural monastery nine miles from Valenciennes, achieved a far more influential and important position in the kingdom than the town of Valenciennes ever did.